Navigating the Qur'anic Generation: Challenges and Opportunities for Non-Formal Islamic Institutions - Robbaniyah, Qiyadah; Lina, Roidah (Universitas Islam Indonesia, 2024)
This study explores the management of non-formal Islamic educational institutions in fostering a Qur’anic generation with strong faith and noble character. Employing a qualitative research approach, the study examines the distinctive educational strategies implemented by various institutions. Specifically, it analyzes the integration of Qur’anic memorization (tahfidz) and entrepreneurship at Rumah Tahfidz An-Nahl, the structured memorization system at Rumah Tahfidz Dar Aisyah, and the combination of skill-based training and Arabic language instruction at LPK Jamilurrahman. Data were collected through in-depth interviews, direct observations, and document analysis. The collected data were then analyzed descriptively to gain insights into the management approaches and challenges faced by these institutions. The findings indicate that the primary challenges include limitations in the availability of qualified educators, inadequate infrastructure, and difficulties in managing student engagement. Each institution employs unique strategies to address these issues, such as involving alumni in teaching roles and implementing supervision systems to maintain discipline and learning quality. Despite these challenges, the study reveals that the unwavering commitment of these institutions to delivering high-quality education rooted in Islamic values remains their core strength. These findings highlight the critical role of non-formal Islamic education in providing relevant and beneficial learning opportunities, contributing significantly to the development of morally upright and competent individuals.